Security in an IPv6 Environment - Minoli, Daniel; Kouns, Jake (Auerbach Publications, 2016)
Analyze Key Security Mechanisms and Approaches with this practical primer, the first book on the market to cover critical IPv6 security considerations. Dan Minoli, author of over 50 books on telecommunications and networks, and Jake Kouns, Chairman, CEO and CFO of the Open Security Foundation, discuss IPv6 security vulnerabilities, considerations, a.